Analisis Hukum Pengaturan Akses Layanan Aman Untuk Tindakan Aborsi Bagi Korban Kekerasan Seksual Dihubungkan Dengan Perlindungan Kesehatan Reproduksi Perempuan Menurut Peraturan Perundang-Undangan di Indonesia - Herman, Vianica; Basani, Christin Septina (University of Merdeka Malang, 2024)
The issue that arises in the regulation of abortion in Law No. 1 of 2023 on the Criminal Code and Law No. 17 of 2023 on Health is the difference in provisions and the scope of regulations held by these two laws. First, Law No. 1 of 2023 on the Criminal Code regulates criminal offenses and the criminal justice system in general, including in the context of abortion. However, the provisions in the Criminal Code tend to be criminalizing in nature, where abortion is often considered a criminal offense. Problems arise when these two laws have conflicting or inconsistent provisions, such as in determining the permissible gestational age limit for performing an abortion, the definition of qualifying health conditions, and the procedures that must be followed. The research method used in this study is the Normative Juridical research method. This study includes the analysis of legal texts, namely the Health Law No. 17 of 2023 and the Criminal Code Law No. 1 of 2023, as well as the interpretation of these two legal regulations. The result of this research is that the Health Law No. 17 of 2023 expands access to abortion services for victims of sexual violence by providing special exceptions in certain situations, such as pregnancies resulting from reported rape. This law establishes more detailed guidelines regarding abortion procedures and gestational age limits. Nevertheless, implementation challenges such as social stigma and limited access to healthcare services still need to be addressed. Meanwhile, Article 463 of the Criminal Code regulates criminal sanctions for abortions performed without complying with legal provisions. Thus, the Health Law No. 17 of 2023 provides guidelines for safe and legal abortions, while the Criminal Code enforces the law against illegal abortionsÂ